The Effect of Educational Film Supported Augmented Reality Applications on Academic Achievement and Motivation for Science Learning - Emre Guvenir; Ezgi Guven-Yildirim (Journal of Education in Science, Environment and Health)
The aim of this research is to investigate the effects of educational film-supported augmented reality applications in the teaching of the Solar System and Eclipses Unit of the 6th grade Science course on the academic success of the students and their motivation levels for learning science. The study group of the research consisted of 42 students attending the 6th grade in Kahramanmaraş in the fall semester of the 2021-2022 academic year. In this research, quasi-experimental design was used. The participants from whom the data were collected were determined by convenient sampling method. The experimental group (N=22) of the study consisted of the learning group with educational film supported augmented reality applications, and the control group (N=20) was the group that studied with the learning method specified in the current science curriculum. The results obtained from the study revealed that there was no significant difference between the achievement test and motivation scale pre-test scores of the experimental and control groups. Another result obtained from the study is that there is a significant difference in favor of the experimental group between the achievement test and motivation scale posttest mean scores of the groups as a result of the application process